A hydrogel directly assembled from a copper metal–organic polyhedron for antimicrobial application. Issue 15 (31st January 2019) - Qin, Yu; Chen, Lin-Lin; Pu, Wei; Liu, Peng; Liu, Shi-Xi; Li, Yuan; Liu, Xiao-Lan; Lu, Zhi-Xiang; Zheng, Li-Yan; Cao, Qiu-E
Abstract : A hydrogel was directly assembled from a Cu-MOP by a facile procedure without adding any polymers for the first time, and it exhibited excellent antibacterial activity towards both Gram-negative and Gram-positive bacteria. Abstract : Here, we report the first example of a hydrogel directly assembled from a copper MOP by a facile ultrasonic procedure, and it exhibited excellent antibacterial activity towards Gram-negative and Gram-positive bacteria.